Towards Effective Information Provision: A Study on Library User Search Patterns and Selection Criteria - Irvan Muliyadi (UPT Perpustakaan UIN Alauddin Makassar, 2023)
Understanding how library users access and utilize information resources is crucial for librarians to enhance their library services. This research delves into the search strategies employed by library users to access information resources and the criteria they use in selecting such resources. The study involves interviews with 20 participants, all final-year students majoring in library science at Alauddin State Islamic University of Makassar. The research reveals that library users commonly employ mental and basic search strategies. This observation underscores the potential drawbacks of relying solely on mental and basic approaches, as it may result in suboptimal outcomes in terms of both quantity and quality of information resources. The study further identifies currency, the minimum acceptable standard, and availability or accessibility as the primary indicators guiding the selection of information resources. Consequently, librarians should ensure that the information resources they provide meet these criteria. The findings emphasize the necessity for librarians to incorporate complex and written search strategies, integral components of information literacy empowerment, into any information literacy program. Additionally, librarians should prioritize the regular updating and accessibility of information resources, recognizing that quality serves as the baseline standard for such resources. Librarians should prioritize updating and accessibility information sources, even if the quality of these sources is at a minimum level.